Opsen Pajak Penerapan Opsen Pajak atas Pajak Daerah sebagai Mekanisme Peningkatan Penerimaan dan Pendapatan Negara ditinjau dari Peraturan Perundang-undangan yang Berlaku - Wulansari, Putri (Unram Law Review, 2023)
The tax sector has a dominant role as the government's fiscal instrument in realizing social welfare. It is because the tax sector is still in the top position as a source of state revenue and revenue. It becomes relevant if the government continues to extensify the collection and calculation of taxes and adds new types of taxes. Thus, state income remains stable and increases. However, this extensification creates problems in society which have the potential to create double taxes and increase the burden of taxes that must be paid, one of which is the regional tax opsen. This research uses a normative juridical approach with a descriptive-analytic type by examining secondary sources as primary data. This research aims to explain the relevance of regional tax opsen for the burden of taxes on taxpayers in Indonesia.